DETERMINANTS OF INTRAUTERINE GROWTH RESTRICTION (IUGR) IN LABOURING MOTHERS AT REGIONAL GENERAL HOSPITAL IN KARAWANG, WEST JAVA - Meigasari Herman; Sahrudi - (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Introduction: Intrauterine Growth Restriction (IUGR) is a problem that continues to be challenging in the care of mothers and newborns. IUGR causes the baby's growth process to be stunted and the baby is born with health problems. Many factors influence the incidence of IUGR, both modifiable and irreversible factors. This study aimed to determine the determinant factors for the incidence of IUGR in labouring mothers at the Karawang Regional General Hospital, West Java. Method: The research design used correlation analysis with a cross-sectional approach. The population in this study were labouring mothers at Karawang Hospital. The sampling technique used systematic random sampling. Bivariate analysis used the Chi-Square test. Results: Hasil penelitian menunjukkan bahwa sebagian besar prevalensi kejadian IUGR pada ibu bersalin adalah 68.8%. Hasil analisis bivariat menunjukkan bahwa terdapat hubungan yang signifikan terhadap kejadian IUGR pada ibu bersalin meliputi usia (p-value = 0.016; Î± <0.05), paritas (p-value = 0.028; Î± <0.05), hipertensi paritas (p-value = 0.044; Î± <0.05), preeklamsia (p-value = 0.048; Î± <0.05), status gizi (p-value = 0.026; Î± <0.05); anemia (p-value = 0.029; Î± <0.05); kehamilan gemelli (p-value = 0.028; Î± <0.05). Tidak terdapat hubungan yang signifikan antara riwayat penyakit jantung dengan IUGR (p-value = 0.532; Î± <0.05). Kesimpulan. IUGR merupakan kondisi yang menyebabkan pertumbuhan janin terhampat. Beberapa faktor yang mempengaruhi IUGR meliputi usia ibu hamil, paritas multipara atau grandemultipara, hipertensi sebagai komorbiditas, preeklamsia, status gizi ibu hamil, anemia saat kehamilan, dan kehamilan gemeli. Sebagian dari faktor risiko tersebut dapat diubah dan dicegah oleh ibu hamil dengan cara melakukan pemeriksaan secara rutin.